The Transformation of Deleh Mendeleh: An ‘Urf-Based Analysis of Reciprocity in Sukowati Village - Rahmadhani, Novi; Al Munawar, Faishal Agil; Saiban, Kasuwi (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This study aims to examine the transformation of the deleh mendeleh tradition within marriage practices in Sukowati Village, Gresik Regency, through the lens of ‘urf in Islamic law. Traditionally regarded as a form of voluntary mutual assistance, empirical findings reveal that the practice has evolved into a socially binding system of reciprocity characterized by systematic record-keeping and expectations of repayment. This qualitative field research involved 10 informants selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and analyzed using thematic analysis. The findings indicate a dual perception within the community. While some participants continue to view deleh mendeleh as an expression of solidarity, others experience it as a social obligation accompanied by economic pressure. Empirical evidence shows that recorded contributions ranging from IDR 50,000 to IDR 500,000 generate repayment expectations that disproportionately burden lower-income households. From the perspective of ‘urf, the practice may be classified as ‘urf ṣaḥīḥ when based on voluntariness and oriented toward ta‘āwun and maṣlaḥah. However, when shaped by social pressure and economic burden, it shifts toward ‘urf fāsid, as it undermines the principles of justice and mutual consent (riḍā). This study contributes to uṣūl al-fiqh discourse by demonstrating that ‘urf is dynamically shaped by processes of social institutionalization, thereby requiring continuous reassessment to ensure its alignment with Islamic legal principles.